Identifying potential genetic counseling program applicant competencies. - Gallant, Alexis; Carmany, Erin; Trepanier, Angela (Journal of Genetic Counseling, 2025)
Genetic counseling (GC) program admission is highly competitive. Developing applicant competencies, like the Association of American Medical Colleges (AAMC) has done, could help genetic counseling applicants better identify the knowledge, skills, and personal qualities programs seek. The purpose of this qualitative focus group study was to develop a set of draft GC program applicant competencies and then compare them with those established by the AAMC. We developed a semi‐structured interview guide that included questions about GC application requirements, the reason for each requirement, and how important each was in evaluating an applicant. These were followed by questions that asked to what extent the medical school applicant competencies aligned with what GC programs were looking for in applicants, and overall thoughts about developing applicant competencies. Focus group participants, which could include program leadership and admissions committee members, were recruited through the Association of Genetic Counseling Program Directors' listserv. Four virtual focus groups were held between December 2020 and February 2021. Fifteen people participated, representing 13 of 50 programs. One investigator conducted the focus group session while the other two investigators took notes. Each focus group session was recorded and then transcribed verbatim. The transcripts and notes were reviewed by each investigator independently to generate themes (applicant competencies) using reflexive thematic analysis. Draft themes were reviewed, discussed, and refined, using two rounds of an iterative process. The draft set of competencies was then sent to focus group participants for review. Comments were submitted by six participants representing all four focus groups and were incorporated. Thirteen competencies, reflective of the baseline knowledge, skills, and personal qualities sought in genetic counseling applicants, were identified: Foundation in Basic Science and Genetics, Insight into the Profession, Academic Ability, Capacity for Self‐Awareness, Interpersonal Skills, Communication Skills, Critical Thinking and Reasoning, Teamwork, Cultural Humility, Professional Attributes, Capacity to Value and Support Diverse Perspectives, Capacity for Growth, and Commitment to Helping Others. These competencies significantly overlap with medical school applicant competencies but also reflect unique aspects of the GC profession. Additional research to evaluate this set of competencies and the pros and cons of using them in GC admissions is needed. We believe that this work serves as a starting place to promote transparency in GC admissions.